2014
DOI: 10.1128/aem.04241-13
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Haa1, Which Is Linked to Its Phosphorylation Status, Mediates Lactic Acid Tolerance in Saccharomyces cerevisiae

Abstract: Improvement of the lactic acid resistance of the yeast Saccharomyces cerevisiae is important for the application of the yeast in industrial production of lactic acid from renewable resources. However, we still do not know the precise mechanisms of the lactic acid adaptation response in yeast and, consequently, lack effective approaches for improving its lactic acid tolerance. To enhance our understanding of the adaptation response, we screened for S. cerevisiae genes that confer enhanced lactic acid resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 43 publications
4
50
1
Order By: Relevance
“…When testing the panel of highly expressed GCN5-regulated genes, we found significant changes in expression, particularly of GPG1 and PHM8 (117 and 68% increases in expression, respectively). Both GPG1 and PHM8 are upregulated by the transcription factor Haa1, which relocalizes to the nucleus upon weak acid stress and in conditions of DNA replication stress (Tkach et al 2012;Sugiyama et al 2014). Coincident with Haa1 nuclear accumulation is loss of phosphorylation (Sugiyama and Nikawa 2001), but the phosphatase has not yet been identified.…”
Section: Gcn5-pp2a Promote Histone Expression 1703mentioning
confidence: 99%
“…When testing the panel of highly expressed GCN5-regulated genes, we found significant changes in expression, particularly of GPG1 and PHM8 (117 and 68% increases in expression, respectively). Both GPG1 and PHM8 are upregulated by the transcription factor Haa1, which relocalizes to the nucleus upon weak acid stress and in conditions of DNA replication stress (Tkach et al 2012;Sugiyama et al 2014). Coincident with Haa1 nuclear accumulation is loss of phosphorylation (Sugiyama and Nikawa 2001), but the phosphatase has not yet been identified.…”
Section: Gcn5-pp2a Promote Histone Expression 1703mentioning
confidence: 99%
“…The presence of acetylated polymers in lignocellulosic biomass implies that the mechanisms of acetic acid tolerance will inevitably remain a key issue in the implementation and diversification of sustainable, non-food feedstocks in industrial biotechnology. While the global mechanisms of acetic acid action and tolerance in yeast cells have been mostly elucidated [38], other toxicogenomic analyses involving the yeast response to weak acids are essential to identify their molecular targets and guide the design of more robust strains for efficient industrial production of organic acids [39].…”
Section: Yeast Toxicogenomics Applied To Environmental and Agriculturmentioning
confidence: 99%
“…Haa1 seems to be also an important determinant of the yeast’s tolerance to acetic acid stress, as the deletion of a significant number of genes of the Haa1-regulon was shown to result in increased susceptibility to acetic acid [7]. Moreover, several recent studies have shown that overexpression of HAA1 improves yeast’s tolerance to high concentrations of acetic and lactic acid [1417]. Given that the deletion of the HAA1 gene was found to lead to a higher accumulation of labeled acetic acid in stressed cells [18], the role of Haa1 is, at least partially, related with its involvement in the reduction of the intracellular acetate concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In response to inhibitory concentrations of lactic acid, Haa1 was found to rapidly migrate from the cytoplasm to the nucleus suggesting that the biological activity of the transcription factor is dependent on its subcellular localization [14]. The Haa1 translocation is accompanied by a decrease in the phosphorylation level of the protein indicating that the transcription factor is activated upon dephosphorylation [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation